2009
DOI: 10.2139/ssrn.1531557
|View full text |Cite
|
Sign up to set email alerts
|

Citation Success: Evidence from Economic History Journal Publications

Abstract: This study examines the determinants of citation success among authors who have recently published their work in economic history journals. Besides offering clues about how to improve one's scientific impact, our citation analysis also sheds light on the state of the field of economic history. Consistent with our expectations, we find that full professors, authors appointed at economics and history departments, and authors working in Anglo-Saxon and German countries are more likely to receive citations than ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
(28 reference statements)
0
14
1
Order By: Relevance
“…Indeed, overall behaviour of citations success in our sample observes (to the naked eye) significantly lower values that those reported by systematic studies of international peer-reviewed journals (such as Di Vaio et al, 2012).…”
contrasting
confidence: 85%
See 3 more Smart Citations
“…Indeed, overall behaviour of citations success in our sample observes (to the naked eye) significantly lower values that those reported by systematic studies of international peer-reviewed journals (such as Di Vaio et al, 2012).…”
contrasting
confidence: 85%
“…This set built upon the 14 outlets on economic history used by Di Vaio et al (2012) 6 , of which nine were found to carry items that met our selection criteria. The dataset compares handsomely with other systematic studies of citation success.…”
Section: Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…The opposite would be true if we only use the first seven years of citations to articles in the earlier sample, but the relative ranking of the journals in that earlier period would remain unchanged. 36 Oswald (2007) Vaio et al (2012). that holds for scholarly journals more generally (Stern 2013).…”
mentioning
confidence: 99%